Model development and simulation for robot-based warehouse automation - Zhang, Yijing (Nanyang Technological University, 2023)
With the boom in the logistics industry and the continuous development of robotics technology, it has become a popular research trend to apply multi-robot systems in warehouses to improve the efficiency of warehousing systems. The key problem in the study of intelligent warehousing systems is to make the multi-robot system reach goal locations safely and quickly. This dissertation studies the path planning problem of the multi-robot systems in the intelligent warehouse environment and a hierarchical conflict-based search algorithm is proposed. The low level of the algorithm uses the space-time A* algorithm, planning an optimal path for each robot individually. The high level performs conflict search and constraint addition based on a binary tree. Considering that some of the commonly used warehouse layouts have oblique main aisles, the low level is allowed to adopt hybrid search methods to improve the efficiency of the system. The feasibility of the conflict-based search algorithm is verified in the MATLAB environment, and the simulation results prove that the proposed algorithm can guarantee the multi-robot system to reach the goal locations without collision at a minimum time cost.